An equation is shown below:

4(x − 3) − 5(x + 1) = 3

Which statement shows a correct next step in solving the equation?

A.) The equation can become 4x − 12 − 5x − 5 = 3 by applying the associative property of multiplication.
B.) The equation can become 4x − 3 − 5x + 1 = 3 by applying the associative property of multiplication.
C.) The equation can become 4x − 3 − 5x + 1 = 3 by applying the distributive property.
D.) The equation can become 4x − 12 − 5x − 5 = 3 by applying the distributive property. ((I CHOSE THIS ANSWER))

Respuesta :

if you need the full answer take this this includes every thing

4(x−3)−5(x+1)=34(x-3)-5(x+1)=34(x−3)−5(x+1)=3
1 Expand
4x−12−5x−5=34x-12-5x-5=34x−12−5x−5=3

2 Simplify 4x−12−5x−54x-12-5x-54x−12−5x−5 to −x−17-x-17−x−17
−x−17=3-x-17=3−x−17=3

3 Add 171717 to both sides
−x=3+17-x=3+17−x=3+17

4 Simplify 3+173+173+17 to 202020
−x=20-x=20−x=20

5 Multiply both sides by −1-1−1
x=−20x=-20x=−20
ACCESS MORE